Sor Juana Inés de la Cruz and the Mirror of Enigmas (Anclajes, 2014)
Sor Juana Ines de la Cruz uses the tradition of typological interpretation of the Bible, which dates back to St. Paul and St. Augustine, to interpret the ancient pagan authors and the Aztecs cults like obscure or enigmatic allegories of the Christianity. This appropriation of pre-Cristian texts and mythology is not linked to the alleged liberal pluralism of the Creoles, as Octavio Paz raised, nor a supposed cultural mix, as Gruzinski arise. Far from an openness to cultural otherness, his gesture is rather an absorption in the Christian sameness.
Keywords: Sor Juana Inés de la Cruz; colonial literature; cultural history; XVII Century; New Spain